FILAMEN LAMPU INCANDESCENT SEBAGAI DETEKSI KEBOCORAN ALIRAN UDARA - Tasdik Darmana; Dery Risky (Sutet, 2016)
Incandescent filament in an incandescent lamp is a prisoner in the form of wire. When electrified, the filaments become very hot, ranging from 2800 degrees Kelvin up to a maximum of 3700 degrees Kelvin. This causes the light emitted by incandescent bulbs is usually a reddish yellow. At extremely high temperatures that the filaments began to produce light at wavelengths that are invisible. If the filament by the air flow will cause a change in resistance value. If there is no air flow, the filament resistance value will be low. If there is airflow, the filament resistance will change vary. Variations caused by differences in heat resistance filament. Resistance variations also affect the voltage variation that passes through the filament. The voltage variation will be processed by the Op-Amp and displayed by LEDs